Ancestral Hopi migrations - Lyons, Patrick D., 1969- (Anthropological papers of the University of Arizona, 2003)
Assesses the scale and impact of ancestral Hopi migrations, including the origin and spread of Roosevelt Red Ware, and examines the archaeological record of Homol'ovi, presenting evidence that the ancient inhabitants of the Winslow, Arizona, area were immigrants from the Hopi Mesas.